2016
DOI: 10.4018/ijssoe.2016070101
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Learning Styles on the Acceptance of Open Learner Models in Collaborative Learning

Abstract: Individual differences in learners' learning styles can have a significant effect on their acceptance of collaboration technologies to facilitate the sharing of learning information in technology-based collaborative learning. There is, however, a lack of understanding of the impact of learning styles on the acceptance of open learner models as a collaboration technology for information sharing. This study investigates the impact of learners' learning styles on their acceptance of open learner models for inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…Because of the exploratory nature of this study, this study adopts a quantitative methodology based on the use of an online survey of smartphone users in China. Surveys are a popular method for acquiring relevant information on behaviors, social characteristics and attitudes of a specific population on a given topic (Bird, 2009; Rhee et al , 2009; Sek et al , 2016). In this study, the use of an online survey can lead to a better understanding of the information security behaviors of smartphone users in China.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the exploratory nature of this study, this study adopts a quantitative methodology based on the use of an online survey of smartphone users in China. Surveys are a popular method for acquiring relevant information on behaviors, social characteristics and attitudes of a specific population on a given topic (Bird, 2009; Rhee et al , 2009; Sek et al , 2016). In this study, the use of an online survey can lead to a better understanding of the information security behaviors of smartphone users in China.…”
Section: Methodsmentioning
confidence: 99%
“…eLearning can be approached from different viewpoints including the educational paradigm and the delivery orientation (Lee, Yoon and Lee, 2009;Sek et al, 2016). Educational philosophers view eLearning as a self-regulated knowledge acquisition practice achieved through various learning processes including interactions using digital technologies (Lee, Yoon and Lee, 2009;Sek et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While extant literature has shown that digital content design affects students' learning (Cabot et al, 2014;Jeong & Yeo, 2014), it fails to elucidate the underlying mechanisms that lead to distinct effects. Additionally, even though studies on kinesthetic learning have increasingly stressed the matching of learning styles between instructors and students (Pritchard, 2017;Sek et al, 2015;Syofyan & Siwi, 2018), they lack adequate exploration of the impact of content design from the standpoint of information delivery. Furthermore, the effectiveness of standardized design norms requires further scrutiny to better regulate content sharing and encourage learners' engagement on CoP platforms (Danieau et al, 2013;Hyman et al, 2014).…”
Section: Introductionmentioning
confidence: 99%